From Raffinose Family Oligosaccharides to Sucrose and Hexoses: Gene Expression Profiles Underlying Host-to-Nematode Carbon Delivery in Cucumis sativus Roots - Wang, Xingyi; Li, Shihui; Zhang, Xu; Gao, Lihong; Ruan, Yong-Ling; Tian, Yongqiang; Ma, Si (Frontiers in Plant Science, 2022)
Root-knot nematodes (Meloidogyne incognita) induce specific feeding sites in cucumber roots where they absorb carbon nutrients from the host, thereby turning the feeding sites into a strong sink for assimilates. Nematode infection may alter host sugar metabolism in the roots of sucrose-transporting species. However, much less is known in species translocating RFOs (raffinose family oligosaccharides), such as cucumber. To address this knowledge gap, we analyzed the dynamics of RFOs and sucrose metabolisms, two major sugar-metabolism processes, in cucumber roots during nematode infection at transcription and protein levels. In the nematode-infected root, the expressions of RFO-synthesis genes, CsRS (Raffinose Synthase) and CsGolS1 (Galactinol Synthase 1), were upregulated at early stage, but were decreased, along with CsSTS (Stachyose Synthase), at late stage, during nematode infection. By contrast, α-galactosidase, hydrolyzing RFOs into sucrose and galactose, whose encoding genes was suppressed (CsaGA2) at early stage and then elevated (CsaGA2, 4 and CsAGA1) at the late stage of nematode infection. Consistently, stachyose level was significantly increased at the early stage but reduced at late stage of infection in comparison with the uninfected roots, with similar trend found for raffinose and galactinol. Moreover, genes encoding sucrose synthase and cell wall invertase were differently expressed in response to nematode infection. Based on the observation and in conjection with information from literature, we hypothesized that RFOs may play a role in protection of roots during the initial stage of infection but could be used by nematode as C nutrients at the late stage.